Conceptualisation of community-based basic nursing education in South Africa: a grounded theory analysis - Gloria Mtshali (AOSIS, 2005)
Community-based education is about a decade old in basic nursing education in South Africa, An extensive review of literature revealed that although CBE was a familiar concept in South Africa, there was however, limited understanding of what this phenomenon means. The purpose of the study was to analyse the concept 'community-based education' with the aim of discovering shared understanding of this phenomenon in basic nursing education within the South African context. Strauss and Corbin's (1990) grounded theory approach was used to guide the research process. The South African Nursing Council's (SANC) education committee, the National Department of Health, human resources division representatives as well as seven nursing education institutions with well-established CBE programmes participated in the study. The data was collected by means o f observations, interviews and document analysis. Purposive sampling and later theoretical sampling was used for selecting interviewees. This resulted in a total o f 45 interviewees. The data collection and initial data analysis took place concurrently. Descriptive analysis followed by conceptual analysis was performed using Strauss and Corbin's model. The findings in this study revealed that community-based education is education that uses the community extensively, especially the under-developed and under-resourced settings, for learning purposes in order to enhance relevance of nursing education to the needs of the South African population. The core discriminatory characteristics o f CBE were found to include; primacy of the community as a learning environment; the early exposure of students to community-based learning experiences; community-based learning experiences dominating the curriculum, exposure to community-based learning experiences throughout the curriculum, vertical sequencing of community-based learning experiences in a curriculum, starting from primary settings to secondary and later tertiary health care settings to facilitate the development of competencies required when serving in all these settings, and lastly, learning through providing service to the underresourced communities. Community involvement and partnership, problem-centred learning, valid assessment of learning emanated as important characteristics of CBE but which were identified as gaps in the existing programmes. Recommendations focused on these gaps as well as to the problem of community-based learning experiences which were mainly concentrated in first and/or second year levels in most o f the programmes.